Changes in Prosecutorial Decision-Making in Response to a High-Profile Mass Shooting - D'Alessio, Stewart J. (American journal of criminal justice, 2024)
While prior studies find that media attention influences how prosecutors handle a specific case, there is a dearth of research examining the impact of media attention on prosecutors’ decision-making in less publicized criminal cases analogous to the publicized case. Using 10 years of data (January 2011 to December 2020) calibrated in monthly intervals obtained from the Broward County State Attorney’s Office and an interrupted time series research design, we investigate the effect of the Parkland mass shooting on prosecutor discretion in firearm-related cases eligible for mandatory minimum sentencing under Florida’s 10–20-Life law. Results show that while the Parkland mass shooting was not associated with the filing of firearm cases or with negotiated plea deals, it had a noteworthy effect on attenuating nolle prossed cases. Firearm defendants were also less apt to have their arrest to filing charge reduced, their arrest to disposition filing charge reduced, and their filing to dispositional charge lessened. Overall, these findings suggest that prosecutors became more punitive in their handling of firearm cases after the Parkland mass shooting.